إعادة التأمين كآلية لإدارة المخاطر في شركات التأمين الجزائرية (دراسة تحليلية للفترة 2016-2021) - حديد, إيمان; خبازي, فاطمة الزهرة (جامعة الوادي - University of Eloued, 2023)
نهدف من خلال الدراسة إلى تبيان دور وأهمية عملية إعادة التأمين في إدارة المخاطر التي تواجه شركات التأمين نظرا لفعالية هذه العملية كوسيلة معتمدة في نقل الخطر وأهميتها في رفع القدرة الاستيعابية للاكتتاب لدى شركات التأمين من جهة وتحملها جزء من أخطار الشركات من جهة أخرى، كل هذا يساهم في تحقيق الاستقرار المالي ويزيد من هامش ملاءتها المالية. توصلنا من خلال الدراسة إلى مجموعة من النتائج أهمها أن عملية إعادة التأمين ألية فعالة في تشتيت وتوزيع أخطار شركات التأمين وهي بمثابة دعامة تحفزها على الزيادة في طاقتها الاكتتابية خاصة وأنها عادة ما تعترضها أخطار تفوق قدرتها حيث لا يمكنها ضمان تغطيتها وتحمل تبعاتها لوحدها Through the study, we aim to demonstrate the role and importance of the reinsurance process in managing the risks facing the insurance companies due to the effectiveness of this process as an approved means in transferring the risk and its importance in raising the absorption capacity of the insurance companies on the one hand and bearing part of the risks of the companies on the other hand, all of this contributes In achieving financial stabilité and increases the margin of its financial solvency. Through the study, we reached a set of results, the most important of which is that the reinsurance process is an effective mechanism in dispersing and distributing the risks of insurance companies.
Reinsurance as a risk management mechanism in Algerian insurance companies (analytical study for the period 2016-2021)
مقال
Keywords: شركات التأمين ; إعادة التأمين ; إدارة المخاطر: Insurance companies; re Insurance; Risk Management